2016
DOI: 10.1080/16070658.2016.1230971
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to implementing the food-based dietary guidelines in the South African primary school curriculum: a qualitative study exploring the perceptions of principals and curriculum advisors

Abstract: Objectives:The South African food-based dietary guidelines (FBDG) were developed and implemented to promote healthy lifestyles in the population along with preventing non-communicable diseases and other forms of diet-related illness. The FBDG were recommended for implementation within the national school curriculum. The objective of this study was to explore perceived challenges to successful implementation of these guidelines in the primary school curriculum. Design: This qualitative study gathered data via s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
1
11
0
6
Order By: Relevance
“…However, there should be different periods allocated for training and development programmes to be conducted for new and old employees. For instance, these findings revealed the need to develop the potentials of new employees by way of pre-service training before taking up the job to enable them acquire the required skills on the one hand, and on the other hand, continuous professional development trainings should be conducted for older staff to improve their competencies periodically through the use of appropriate local resources (Hager et al 2016 :746; Nguyen et al 2017 :18; Pagnotta et al 2016 :297; Reilly et al 2017 :218; Weatherson et al 2017 :835). Thus, if sustainable knowledge on school health policies and awareness creation programmes are designed and adopted, the potentials of different role-players would be developed, and they will be empowered for the effective dissemination and implementation of a policy on school health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there should be different periods allocated for training and development programmes to be conducted for new and old employees. For instance, these findings revealed the need to develop the potentials of new employees by way of pre-service training before taking up the job to enable them acquire the required skills on the one hand, and on the other hand, continuous professional development trainings should be conducted for older staff to improve their competencies periodically through the use of appropriate local resources (Hager et al 2016 :746; Nguyen et al 2017 :18; Pagnotta et al 2016 :297; Reilly et al 2017 :218; Weatherson et al 2017 :835). Thus, if sustainable knowledge on school health policies and awareness creation programmes are designed and adopted, the potentials of different role-players would be developed, and they will be empowered for the effective dissemination and implementation of a policy on school health.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that information on the dissemination and implementation of a policy on school health should be shared openly and effectively amongst stakeholders without citing any specific evidence (Larsen et al 2017 :40; Larson et al 2017 :208; Montague et al 2014 :3; Tapia et al 2017 :528; Weatherson et al 2017 :835). Other studies have considered feedback, telephone calls, consultations, dialogue and referral as evidences (Leow et al 2014 :108; Nguyen et al 2017 :18; Vanneste et al 2016 :6; Weatherson et al 2017 :83). For instance, dialogue, as a means of sharing information to promote active participation of stakeholders was mentioned by Vanneste et al ( 2016 :6).…”
Section: Theme 1: Information Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…[38] According to a regional qualitative study, many barriers exist that hinder the successful implementation of nutrition education in the curriculum. [44] Since there has been insufficient progress in establishing healthy school nutrition culture and environment, a grade of D-was assigned. NSNP C The NSNP has wide reach, providing meals to >9 million children in public schools (all children in quintiles 1 -3).…”
Section: D-mentioning
confidence: 99%
“…We used a non-quantified validated indicator food frequency questionnaire (IFFQ) 12 have raised the issue that educators' weight status and eating behaviors are potential challenges to teaching food-based dietary guidelines. 10 When school principals were interviewed regarding the health challenges of learners, educators and caregivers, they identified substance abuse, tobacco use and overweight as the top health priorities for caregivers in these socio-economically disadvantaged South African communities. 6 The aim of our study was to develop a profile of modifiable risk factors for NCDs in the caregiv- For data analysis, the indicator foods were assigned to six food categories, namely: 1) fruit and vegetables; 2) high fat foods (such as processed meats; yellow cheese; margarine; fried foods, take-outs, and pastries); 3) energy-dense snacks/ items (such as sugar, chocolate, cake, crisps, sweetened beverages); 4) white bread and starches; 5) brown bread, legumes, high fiber cereals ; 6) processed (high salt/high fat) foods (tinned meat/fish, bread, margarine, cheese, crisps, take outs, eg, fast foods, pies).…”
Section: Dietary Intake Sectionmentioning
confidence: 99%